NOOTROPIC EFFECT OF COMPLEX PHYTOREMEDY «NOOPHYT» EXTRACT - N. Ts. Bazarova; Ya. G. Razuvayeva; S. M. Nikolayev; I. G. Nikolayeva; I. P. Ubeyeva (Acta Biomedica Scientifica)
In experiments on white rats (Wistar line) it was found that the dry extract of phytoremedy «Noophyt» pronounced nootropic effect. «Noophyt» extract in a volume of 0,2 and 0,5 ml/100 g simulated the development of conditioned reflexes of active and passive avoiding and caused to the saving of a memorable trace in the kept away terms after training оf intact animals and also in a volume of 0.5 ml/100g has a marked effect on the background antiamnesic skopolaminovoy amnesia.